The role of alimentary and biliopancreatic limb length in outcomes of Roux-en-Y gastric bypass - Darabi, Sattar (Wideochir Inne Tech Maloinwazyjne, 2019)
INTRODUCTION: Roux-en-Y gastric bypass (RYGB) is one of the safe and easily reproducible bariatric procedures. AIM: To evaluate the effect of biliopancreatic limb (BPL) and alimentary limb (AL) length on weight loss outcomes after RYGB. MATERIAL AND METHODS: This retrospective cohort study included 313 morbidly obese patients who underwent primary laparoscopic RYGB 2009–2015. Patients’ BPL and AL lengths were categorized into three groups: group 1 (BPL: 50 cm and AL: 150 cm), group 2 (BPL: 150 cm and AL: 50 cm), and group 3 (BPL: 100 cm and AL: 100 cm). Data were provided from the Iranian National Obesity Surgery Database. The generalized estimating equations method was used to assess the effect of limbs length on %excess weight loss (%EWL). RESULTS: Mean ± standard deviation age and body mass index (BMI) of 252 patients were 38.55 ±10.24 years and 45.8 ±4.77 kg/m(2), respectively. Totally, 172 (68.3%, BMI of 46 ±5 kg/m(2)), 48 (19%, BMI of 45.12 ±4.26 kg/m(2)), and 32 (12.7%, BMI of 45.43 ±4.23 kg/m(2)) were in group 1, 2, and 3, respectively (p = 0.44). The results showed that the choice of different limb lengths had no significant effect on %EWL over 12 months follow-up (p = 0.625) adjusted for baseline BMI (p = 0.25). Mean %EWL in the patients with longer BPL and shorter AL was 5.43% (1.91, 8.95) higher in comparison to the patients with shorter BPL and longer AL during 36 months postoperatively adjusted for baseline BMI (p = 0.002). CONCLUSIONS: During 12 months after RYGB, %EWL was not associated with BPL or AL length. However, during 36 months postoperatively, the patients with longer BPL had a significantly higher %EWL in comparison to the patients with shorter BPL.